2022
DOI: 10.1007/s44205-022-00021-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of ion magnetization on plasma generation in a magnetic nozzle rf device

Abstract: Two dimensional mappings of the floating potential, Ar II emission and ion saturation currents are used to characterize an 80 cm long magnetized rf plasma column. The data brings new evidence supporting that the level of ion magnetization under the rf loop antenna plays an important role for the efficient generation of plasma over an extended region when the magnetic nozzle is sufficiently separated from the antenna. Densities up to $$10^{18}$$ 10 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The antenna-magnetic mirror separation of z B = 30 cm was found to maximise the plasma generation under the solenoids in the converging-diverging plasma column when B 0 is greater than a threshold value of 250 G. For B 0 below this threshold, the maximum achieved density is reduced and the axial density profile is bimodal with one maximum under the antenna and one under the solenoids. It was shown that these features and the plasma parameters absolute values were closely maintained when changing the antenna and radiofrequency to a single-loop antenna driven at 27.12 MHz [28,37].…”
Section: Plasma Discharge Characteristicsmentioning
confidence: 92%
See 1 more Smart Citation
“…The antenna-magnetic mirror separation of z B = 30 cm was found to maximise the plasma generation under the solenoids in the converging-diverging plasma column when B 0 is greater than a threshold value of 250 G. For B 0 below this threshold, the maximum achieved density is reduced and the axial density profile is bimodal with one maximum under the antenna and one under the solenoids. It was shown that these features and the plasma parameters absolute values were closely maintained when changing the antenna and radiofrequency to a single-loop antenna driven at 27.12 MHz [28,37].…”
Section: Plasma Discharge Characteristicsmentioning
confidence: 92%
“…Argon I and II emissions at 750.4 nm and 488 nm are measured with a previously described arrangement made out of two 10 nm narrow-band-pass filters and a calibrated CMOS sensor [37]. A feature of optical emission spectroscopy (OES) is that the intensity of emission lines can be interpreted in terms of the density and temperature of the particles contributing to their excitation.…”
Section: Plasma Diagnosticsmentioning
confidence: 99%
“…The data used in this study has been acquired using Moa 31 , a radio-frequency plasma reactor that is an expansion of Huia 32,33 . It consists of a 150 cm long, 9 cm inner diameter borosilicate glass tube plasma source connected to a 70 cm long, 50 cm diameter steel expansion chamber hosting the pumping system and the pressure gauges.…”
Section: A Apparatusmentioning
confidence: 99%
“…5. tions create an inductively coupled plasma exhibiting a symmetrical single peaked axial plasma density gradient ranging from 10 12 cm −3 under the solenoids to 10 10 cm −3 at the extremities of the glass tube 32,33,53 . The LP was placed on axis halfway between the antenna and the solenoids.…”
Section: Electron-energy Probability Function (Eepf)mentioning
confidence: 99%
“…the location of plasma excitation coincides with the magnetic nozzle throat), the experiments presented herein are conducted in an RF plasma device in which the antenna and the coils are not placed on the same axial location (see figure 3). Studies with a similar experimental design have been carried out by [16,21,29,[31][32][33][34]. In this configuration, the plasma is created remotely with respect to the magnetic nozzle throat.…”
Section: Introductionmentioning
confidence: 99%